Geoheritage 2. Examples of Geoeducation, Geoconservation and Geo-rescue Projects in Ontario - Donaldson, J. (Geoscience Canada, 2009)
SUMMARY Three case studies presented here outline the progress of projects recently initiated to improve public appreciation of the diversity, complexity and significance of Earth history, with an emphasis on the importance of such knowledge to humanity. Work on two of these projects has highlighted the paucity of legal protection for significant geological records as well as the frequent loss of basic geoscience data during construction-related landscape modification. These three case studies in promoting geoheritage awareness and geoconservation reinforce the need for the Canadian geoscience community to seek improved legal instruments for the protection of sites of geological and geomorphological importance, and to seek improved procedures for the documentation of information that too commonly is irretrievably lost during major construction projects.